Utilization of Trichoderma viride to Increase Patchouli Alcohol from Crude Extract of Acehnese Patchouli Leaves - Hardjo, Popy Hartatie; Askitosari, Theresia Desy; Wijaya, Agnes Natalia; Edbert, Joshua; Artadana, Ida Bagus Made; Wittayathanarattana, Takon (Biosaintifika: Journal of Biology & Biology Education, 2024)
Acehnese Patchouli var. Sidikalang can produce patchouli oil, one of the country's sources of foreign exchange, and it is advantageous in many industries. However, patchouli alcohol (PA) content in patchouli oil is still low. The higher PA content determines the better quality of patchouli oil. So, delignification with Trichoderma viride was carried out to increase PA and yield of patchouli oil. The duration of delignification patchouli leaves is one factor affecting the increase in PA and yield. This study aimed to determine the effect of delignification duration on PA content and yield. The research method was completely randomized with 8 treatments (a combination of 2 treatments: with and without delignification, and 4 delignification durations: 0, 3, 6, and 9 days). The inoculum used for delignification was an inoculum ball, and then patchouli leaf samples were extracted using microwave-assisted extraction (MAE). Gas chromatography was carried out for PA analysis. Delignification of patchouli leaves, with a delignification time of 9 days, showed high PA and yield, which were (0.3129 ± 0.1557)% and (1.4543 ± 0.7717)%, respectively. The success of delignification at  9 days was also shown by increased phenolic content. Trichoderma viride is often utilized in delignification process, but the optimal duration of its delignification of Aceh patchouli leaves that can help improve patchouli oil quality is not yet known. This research is hoped to help related industries improve the secondary metabolites of plants, which has many benefits for the community. Implication/benefit for science development/society.